ANALISIS WAKAMONO KOTOBA DALAM ANIME SK8 THE INFINITY - Jotika; Afrianty, Rani (Universitas Negeri Jakarta, 2024)
Abstract: Wakamono kotoba is slang used by young Japanese people. This research analyzes the use and examples of wakamono kotoba in the anime SK8 The Infinity, this anime story focuses on skateboarding competitions and the story of the friendship of anime characters. The theory used in this research is sociolinguistic theory. The research method used is qualitative research by analyzing the conversational dialogue of anime characters. The results of the research show that wakamono kotoba has characteristics in its pronunciation and use that describe feelings of admiration, tension, or surprise and used with close friends.